Medieval heresies : Christianity, Judaism, and Islam - Ames, Christine Caldwell (2015)
"Christianity, Judaism, and Islam is the first comparative survey of heresy and its response throughout the medieval world"--
Machine generated contents note: Introduction: 'My community will be divided': heresy in the medieval world; 1. Peoples of the book (380-661); 2. Triumphs of orthodoxy (661-1031); 3. The perfect hatred (1031-1209); 4. Cinders and ashes (1209-1328); 5. Purity and peoples (1328-1510); Epilogue; For further reading; Glossary; Index.
Includes bibliographical references and index.
Keywords: Christian heresies -- History -- Middle Ages, 600-1500.; Jewish heresies -- History -- To 1500.; Islamic heresies -- History -- To 1500.; Christianity and other religions; HISTORY / Europe / General